EFFECT OF FSH β-SUB UNIT AND FSHR GENES POLYMORPHISMS ON SUPEROVULATORY RESPONSE TRAITS - Andreas, E.; Arifiantini, I.; Saputra, F.; Ishak, A. B. L.; Imron, M.; Sumantri, C. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
Follicle stimulating hormone (FSH) is a pituitary expressed glycoprotein hormone that regulatesreproduction in mammals which composed of α and β-sub unit. The β-sub unit dictates its bindingspecificity with their receptor (FSHR). This study aimed to identify polymorphism of FSH β-sub unitand FSHR genes, and its effect to superovulatory response traits on superovulated cows. Study was doneon 32 cows including Angus, Friesian Holstein (FH), Limousin, Simmental and Brahman in CipelangLivestock Embryo Center. Cows used have been treated superovulation and mated by artificialinsemination. Superovulation response (SR), ovulation rate (OR), fertilization percentage (FP) andviable transfer embryo percentage (VP) were analyzed to investigate the effect of FSH β-sub unit andFSHR polymorphism. Allele frequency of FSH β-sub unit|PstI and FSH|AluI were opposite withinspecies. Mostly B allele and C allele for FSH β-sub unit and FSHR respectively have a high number inBos taurus species while those were in contrast in Bos indicus species. The highest heterozygosity wasfound in FH cattle (0.250) for FSH β-sub unit and Brahman (0.333) for FSHR. Significant effect was found between FSHR gene polymorphism with ovulation rate where CC genotype was higher (P<0.05)than CG and GG genotypes.